EMPLOYEE DATA PROCESSING FACILITIES IN PT.SANDI - Fairlyandy Fairlyandy; Eko Hardiyanto SSi, MM Eko Hardiyanto SSi, MM (Jurnal Sistem Informasi, 1999)
Data processing system is needed for a system-oriented data and information. Interrelated and operate to achieve some goal or objective.